Algebraic Reasoning of Student with Keirsey Personality Type in Solving Mathematical Problem - Intan Fathimah Ahmadah (EduMa: Mathematics education learning and teaching, 2020)
Algebraic reasoning is an important skill for students to support in learning mathematics, especially on algebraic topics. This research is aimed at describing students’ algebraic reasoning to solve problems based on Keirsey's personality types. This research used qualitative with a descriptive approach and was conducted involving four students who have equal mathematical abilities and the same gender. The selected students represented Keirsey’s personality types. The selection of students was carried out through two types of tests, namely the Keirsey Temperament Sorter (KTS) and the Mathematics Ability Test (MAT). The result showed that students with Guardian and Idealist personality types liked to use regular and coherent procedures to solve the problem. Then, students with rational and artisan personality types prefer to use complete explanations. So, teachers can improve students' algebraic reasoning skills by facilitating each student based on their personality type, such as developing learning activities that can include every student's algebraic reasoning ability